1975
DOI: 10.2478/cttr-2013-0386
|View full text |Cite
|
Sign up to set email alerts
|

Residue Levels of Fatty Compounds and Surfactants as Suckering Agents on Tobacco

Abstract: Fatty compounds including lauryI alcohol and methyl laurate and Tween 20 surfactant (polyoxyethylene [20] sorbitan monolaurate) and Tween 80 surfactant (polyoxyethylene [20] sorbitan monooleate) with 14C-labelling at various positions were used as suckering agents for Maryland, Burley, and bright tobacco types (Nicotiana tabacum L.) and their residues on the tobacco determined. An average residue of 1.61 ppm of fatty compounds and 1.0 ppm of surfactants were found. The combined totaI of 2.6 ppm residue due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Besides containing these mixed-function derivatives, the surfactants also contain free polyoxyethylene. Previous studies (7) with Tween 80-14 C-1-fatty acid and 14 C-U**-ethylene oxide applied to various classes of field-grown tobacco have shown that calculated residue levels ranged from about 0.41 to 1.45 ppm. These levels may reflect the residues of either the mixed-function derivatives or the free polyoxyethylene, depending on whether the label was on the fatty-acid moiety or on ethylene oxide.…”
Section: Introductionmentioning
confidence: 97%
“…Besides containing these mixed-function derivatives, the surfactants also contain free polyoxyethylene. Previous studies (7) with Tween 80-14 C-1-fatty acid and 14 C-U**-ethylene oxide applied to various classes of field-grown tobacco have shown that calculated residue levels ranged from about 0.41 to 1.45 ppm. These levels may reflect the residues of either the mixed-function derivatives or the free polyoxyethylene, depending on whether the label was on the fatty-acid moiety or on ethylene oxide.…”
Section: Introductionmentioning
confidence: 97%
“…The fatty acid derivatives are not translocated, and their action is probably by localized destruction of cell membranes and tissue kill. Fatty acid residues on tobacco were not detected 26 days after treatment in one study (69) and were found only at about 1 ppm in another (70).…”
Section: Contact Sucker Control and Pinching Agentsmentioning
confidence: 99%